Effects of 810 nm treatments in acute myofiber contraction of C2C12 myotubes - Nashwa Cheema; Linh Pham; Alexa Nazarian; Namrata Ghag; Emma Wise; Christiane Fuchs; Richard Rox Anderson; Joshua Tam (PLoS ONE, 2025)
The muscoskeletal system can be irradiated with wavelengths in the red and near infrared regions which penetrate deep into the body and stimulate biological mechanisms. However, the activation of cellular responses in muscle, specifically actively contracting, is not clearly understood. Therefore, we investigated biological effects induced by irradiation with 810 nm wavelength of light in myotubes, resting or actively contracting in an acute model of exercise. In resting myotubes, cytosolic Ca2+ rose within 10 minutes post treatment with 810 nm at 2–4 J/cm2. ATP production was increased 4% ± 3 at 24 hrs post light treatment. In contracting myotubes, 810 nm treatment resulted in a significant ~30% increase in intracellular ATP levels and a 20% ± 12 reduction in lactate secretion into cell culture media. 810 nm treated myotubes also had a smaller change in myotube width during contractions, 5% ± 3, suggesting the myotubes were contracting with less force. Although the contractile motion was reduced, 810 nm treated myotubes had a higher frequency of spontaneous contractions after removal of electric pulse stimulation (EPS), 42% ± 21 and 1.3-2 – fold increase in mitochondrial proteins, Tom70, citrate synthase (CS) and succinate dehydrogenase (SDHA). This finding suggests that 810 nm treatment altered metabolic and contractile properties of myotubes due to mitochondrial activation. A more thorough understanding of these effects could lead to new treatment modalities that could improve physical performance.